Incidence of Cutaneous Leishmaniasis in Hail Government and its Surrounding Villages - KSA - Alageel, A; Aldahailan, AA; Almansory, AN; Albnayah, AA; Alanzy, G.A; Alshamri, sh (Arab Journal for Sciences and Research Publishing, 2016)
To explore the incidence of cutaneous leishmaniasis in Hail government. Methods: A retrospective study was conducted in Hail governorate and its surrounding villages from 2014 to 2015. Data was based on available records in the dermatology services of King Khalid hospital (KKH) and SPSS was used in data analysis. Results: The overall incidence of cutaneous lieshmaniasis was 125 cases during 2014 and 2015 (12.5%), being more in males than females. The incidence rate of CL started to decrease from 88( 70.4% )cases in 2014 to about 37 (29.6%) in 2015 year .The highest prevalence was in adults (68%), and it was more in Saudi patients than non-Saudis. According to the residence, Hail City (64%) is more affected for CL than its villages (36%). The present study through light that CL is still an endemic disease in Hail city, but its incidence is fortunately declining. Conclusion: cutaneous leishmaniasis is still considered an endemic disease in Hail, Saudi Arabia even though its incidence is declining.
Keywords: Incidence; cutaneous leishmaniasis; Hail; Saudi Arabia